Identification of Bioactive Molecules from Combretum micranthum as Potential Inhibitors of α-amylase through Computational Investigations - Damilola Samuel Bodun; Damilola Alex Omoboyowa; Toheeb Adewale Balogun; Abigail Osinachi Enyinnaya (Journal of Molecular Docking, 2022)
The rising prevalence of diabetes necessitates continued research into natural antidiabetic medicines that target a key biochemical enzyme involved. The α-amylase enzyme is involved in the digestion of starch, glycogen, and disaccharides in the gastrointestinal tract. Its essential roles and distinct properties make it an effective antidiabetic target. This work aimed to use in silico approaches to find possible α-amylase inhibitors from Combretum micranthum bioactive substances. On the Schrödinger Maestro 12.5, over 50 C. micranthum compounds were screened, followed by MM-GBSA and ADMET (absorption, distribution, metabolism, excretion, and toxicity) studies of the highest affinity compounds. The α-amylase binding affinities were higher for rutin trihydrate and myricetin-3-rutinoside (-12.162 kcal/mol and -10.935 kcal/mol, respectively). They reacted with amino acids that are required for the inhibition of α-amylase. As a result, these compounds have the structural characteristics, binding affinities, and molecular interactions necessary as α-amylase inhibitors and could be turned into antidiabetic medicines through lead optimization and experimental research.